Modification and Innovation of Commode Chair Using a Polyester-based Composite for Elderly Patient - Sosiati, Harini; Wahyono, Tri; Hidayatullah, Hidayatullah; Muttaqien, Arif Rahman; Pamasti, Ankas; Wicaksono, Ryan Nauval; Ramadhan, Rahmat (Media Karya Kesehatan, 2024)
Bamboo stems, a source of fiber/bamboo salts, is a type of natural fiber with a lower density than other natural fibers. Apus bamboo is a type of bamboo having high mechanical strength. Their superior properties have attracted public interest to develop their potential to become advanced and functional materials. A combination of woven apus bamboo slats obtained from Kalisemo village, Purworejo Regency, Indonesia, and woven glass fiber are used as the reinforcing material and fabricated to be the hybrid composite material with a polyester binder mixed with 5% eggshell powder. The ratio of reinforcement and binder is 20: 80 (vol. %). This composite product is used for modification and innovation components in the commode chair product as a medical device for elderly patients. The flexural strength and water absorption tests are conducted on the composite material before use. The commercial commode chair made of wood is modified using the composite and made an innovation by adding right and left handrails to maintain the body balance of elderly patients. Keywords: (bamboo slat, commode chair, composite, glass fiber, polyester).